Mucoadhesive, antioxidant, and lubricant catechol-functionalized poly(phosphobetaine) as biomaterial nanotherapeutics for treating ocular dryness - Hoang Linh Bui; Yun-Han Su; Chia-Jung Yang; Chun-Jen Huang; Jui-Yang Lai (Journal of Nanobiotechnology, 2024)
Abstract Dry eye disease (DED) is associated with ocular hyperosmolarity and inflammation. The marketed topical eye drops for DED treatment often lack bioavailability and precorneal residence time. In this study, we investigated catechol-functionalized polyzwitterion p(MPC-co-DMA), composed of 2-methacryloyloxyethyl phosphorylcholine (MPC) and dopamine methacrylamide (DMA) monomers, as potential topical nanotherapeutics for DED. The copolymers were synthesized via random free-radical copolymerization, producing different proportions of catecholic functionalization. All as-prepared polymer compositions displayed good ocular biocompatibility. At a feeding ratio of 1:1, p(MPC1-co-DMA1) can facilitate a robust mucoadhesion via Michael addition and/or Schiff base reaction, thus prolonging ocular residence time after 4 days of topical instillation. The hydration lubrication of MPC and radical-scavenging DMA endow the nano-agent to ease tear-film hyperosmolarity and corneal inflammation. A single dose of p(MPC1-co-DMA1) (1 mg/mL) after 4 days post-instillation can protect the cornea against reactive oxygen species, inhibiting cell apoptosis and the over-expression of pro-inflammatory factors (IL-6 and TNF-α). In clinical assessment, DED-induced rabbit eyes receiving p(MPC1-co-DMA1) could increase lacrimal fluid secretion by 5-fold higher than cyclosporine A. The catechol-functionalized polyzwitterion with enhanced lubricity, mucoadhesion, and anti-oxidation/anti-inflammation properties has shown high promise as a bioactive eye drop formulation for treating DED.